Using E-Module in Guidance Lessons to Enhance Multicultural Self-Efficacy of Islamic and Public High School Students - Yosef Yosef; Fadhlina Rozzaqyah; Rahmi Rahmi; Alika S Marwah; Vin Vilala (Islamic Guidance and Counseling Journal, 2023)
The implication of multiculturally Islamic and public high schools for guidance and counseling was how to help students enhance multicultural self-efficacy using self-learning electronic based-materials. The current study examined the effect of using an e-module of guidance lessons on students' multicultural self-efficacy. It constituted 10th graders of an Islamic High School (IHS) and a Public High School (PHS) as its samples. A Multicultural Self-Efficacy Scale (MSES) was employed to measure students' multicultural self-efficacy before and after completing the self-instruction of the guidance lesson comprising five units of an e-module. The study analyzed the data sets employing a paired sample t-test, independent t-tests, and N-gain techniques to test the hypotheses. The results revealed the significant effect of using the e-module on the multicultural self-efficacy of Islamic and public high school students, no significant differences between the multicultural self-efficacy of IHS and PBS students, and the value of using the e-module was at a moderate level for both groups. In conclusion, using the e-module could provide a functional account of guidance lessons to increase multicultural self-efficacy among students of IHS and PHS.